Catastrophic and exorbitant out-of-pocket expenses during COVID-19 hospitalization in the Encarnación public sector in 2021 (Journal on studies and research of academic knowledge, 2022)
The Paraguayan population faced the pandemic with a segmented health system and a predominance of out-of-pocket spending as financing. The objective of the study was to estimate the incidence and magnitude of out-of-pocket expenses during hospitalization for COVID-19 at the Integrated Hospital of Encarnacion (IPS). As material and method, a quantitative, cross-sectional, descriptive study was implemented between April and July 2021, collecting information on 181 patients from key informants. Excessive, catastrophic and exorbitant spending was defined when out-of-pocket spending was greater than 10%, 25%, and 250% of household income, respectively. The results indicated that 100% had out-of-pocket expenses during their stay in the hospital, averaging 12.9 million Gs. (DE 15.5). The incidence of excessive, catastrophic and exorbitant spending was 98.90%, 94.48% and 51.38% of the cases respectively. The magnitude of out-of-pocket expenses was statistically significantly associated with admission to the intensive care unit but not with having insurance. In conclusion, the health system arrangements were insufficient to avoid catastrophic expenses in the face of COVID-19.
Keywords: out-of-pocket-health spending; catastrophic spending; COVID-19